Occurrence of Pythium Species in Cultivated Soils in the West Bank and Gaza Strip: A Preliminary Report - Mohammed S. Ali-Shtayeh (My University, 1986)
The Pythium flora of 38 soils from different sections of the West Bank and Gaza Strip was determined using a selective agar medium and a surface - soil - dilution plating technique. A total of 23 species were recovered. Sixteen of these species possessed subglobose sporangia and/or hyphal swellings and constituted 92 % of the total number of Pythium propagules. The remaining species had filamentous or lobulate sporangia. Considerable differences in population levels in the different localities were found. The Nablus locality harboured the highest mean level of Pythium propagules followed by the localities in Jenin, Bethlehem, Jericho, Tulkarm, Ramallah, Gaza Strip, and Hebron. Solis in the different localities differed also in population levels and composition of species. Associations between Pythium population levels and soil factors and agricultural practices are discussed.